Eye of the storm : NASA, drones, and the race to crack the hurricane code - Cherrix, Amy E. (Scientists in the field., 2017)
Describes the ways in which technology is being used to study hurricanes in order to predict both the timing and strength of these storms, focusing on NASA's Hurricane and Severe Storm Sentinel mission (HS3) mission that uses drone technology.